2018
DOI: 10.3389/fneur.2018.00364
|View full text |Cite
|
Sign up to set email alerts
|

Brain Structural and Perfusion Signature of Amyotrophic Lateral Sclerosis With Varying Levels of Cognitive Deficit

Abstract: ObjectiveTo characterize the patterns of brain atrophy and perfusion as measured by arterial spin labeling (ASL)-MRI, in amyotrophic lateral sclerosis (ALS) patients with varying levels of cognitive deficit, including ALS with frontotemporal dementia (FTD).MethodsA total of 55 ALS patients and 20 healthy controls (HCs) were included, and all participants underwent neuropsychological assessments and MRI scans. According to their cognitive performance, ALS patients were further subclassified into ALS with normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 52 publications
3
23
0
Order By: Relevance
“…In line with our results, previous studies have constantly found ALS-associated cortical thinning [4,6], hypometabolism [41], and reduced restingstate neural activity [13] in the posterior cingulate cortex. Consistent with our finding of FD reduction in the insula, researchers have described insula impairment in ALS, such as cortical thinning [5], energy hypometabolism [47], and decreased cerebral blood flow [43]. Given that the posterior cingulate cortex and insula are functionally associated with several high-order cognitive processes such as memory and attention [48][49][50][51], it is speculated that FD reduction in these brain regions may be the neurobiological bases of the cognitive dysfunctions in ALS.…”
Section: Biomed Research Internationalsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with our results, previous studies have constantly found ALS-associated cortical thinning [4,6], hypometabolism [41], and reduced restingstate neural activity [13] in the posterior cingulate cortex. Consistent with our finding of FD reduction in the insula, researchers have described insula impairment in ALS, such as cortical thinning [5], energy hypometabolism [47], and decreased cerebral blood flow [43]. Given that the posterior cingulate cortex and insula are functionally associated with several high-order cognitive processes such as memory and attention [48][49][50][51], it is speculated that FD reduction in these brain regions may be the neurobiological bases of the cognitive dysfunctions in ALS.…”
Section: Biomed Research Internationalsupporting
confidence: 89%
“…We also observed a decline of FD in the cingulate gyrus and sulcus (middle part). In fact, middle cingulumassociated cortical atrophy [13,43], functional disconnection [44], and hypoperfusion [43] have been observed in ALS. The middle cingulate cortex has widespread connection with the motor cortex and spinal cord, as well as numerous pyramidal neurons [45].…”
Section: Biomed Research Internationalmentioning
confidence: 99%
“…Whilst neuroimaging studies have demonstrated abnormal CSF dynamics in ALS patients, further studies may be required to specifically determine the influence of these different factors on glymphatic clearance in ALS patients 199]. Abnormal vascular changes in ALS and FTD have further been evidenced through arterial-spin coupling [53,177]. In the SOD1 mouse model, blood-spinal cord barrier (BSCB) breakdown may precede hypoperfusion [215], a feature which has previously been linked to disease severity in ALS patients [2,40].…”
Section: Abnormal Vascular Changes In Alsmentioning
confidence: 99%
“…Multiple studies employing single-photon emission computed tomography (SPECT) have demonstrated hypoperfusion in the brain of both ALS and FTD patients, with greater involvement of the frontal and temporal lobes [ 1 , 82 , 199 ]. Abnormal vascular changes in ALS and FTD have further been evidenced through arterial-spin coupling [ 53 , 177 ]. In the SOD1 mouse model, blood-spinal cord barrier (BSCB) breakdown may precede hypoperfusion [ 215 ], a feature which has previously been linked to disease severity in ALS patients [ 2 , 40 ].…”
Section: Abnormal Vascular Changes In Alsmentioning
confidence: 99%
“…As an effective index to measure local brain activity, amplitude of low frequency fluctuation (ALFF) (Guo et al 2012;Liu et al 2013;Yu-Feng et al 2007) has been extensively employed in ALS research. Using this approach, scholars have discovered that patients with ALS showed aberrant activation in the precentral gyrus, frontal gyrus, and occipital regions; this finding suggests that ALS is a disease involving many system with brain impairment spreading beyond the motor cortex (Bueno et al 2019;Ma et al 2016;Shen et al 2018). In addition, the increased ALFF in the frontal lobe could be a candidate biomarker in ALS (Luo et al 2012).…”
Section: Introductionmentioning
confidence: 99%